Partial Replacement of Stone Dust as Fine Aggregate in Concrete (International Journal of Innovative Research in Engineering & Management, 2022)
The choice to carry out this investigation  was made in response to the fact that natural aggregate  (coarse and fine) that complies with Indian Standards is  currently getting harder to find and more expensive because  of its delayed availability caused by land use regulations,  illegal dredging associated with the sand mafia, and  accessibility to the river source during the rainy season. In  light of this, a study was done to see what would happen if  natural sand were largely replaced with stone dust in  concrete. An experimental program using partial  replacements of fine aggregate with stone dust at 30%,  40%, 50%, 60%, and 70% was undertaken for concrete of  M25 grade with a 0.46 water cement ratio. In this  investigation, sets of cubes and beams were cast for  compressive.
Keywords: Concrete; compressive strength; fine aggregate; split tensile strength; stone dust; moist curing